MODEL DAN PELUANG TERJADINYA HUJAN BERDASARKAN KELEMBABAN MENGGUNAKAN REGRESI LOGISTIK BINER DI KABUPATEN MANOKWARI - Inayatul Farach Ardianty; Indah Ratih Anggriyani (Jurnal Natural, 2020)
Manokwari Regrency has a tropical climate. This results in significant rainfall. One factor that stimulates rain is humidity. By using binary logistic regression, the model an chance of rainfall based on humidity can be determined. Logistic regression analysis is used to determine the relationship between categorical scale response variables and numeric or categoric scale explanatory variables. If response variable used is nominal scale with two possoble value (0 and 1), then it is called binary logistic regression. Estimation of the model is done by logit transformation. The model produce in this study is g(x) = -23.443 + 0.289 humidity. The accuracy of the model is 70.4 percent and the probability of rain for humidity lowering one unit will be reduced to 0.74.